¿Tienen derechos los muertos? - Cárdenas Krenz, Ronald (2020)
The study reviews some common concepts about Law, such as the paradigm that the person becomes an object with death, laying down in question the traditional idea that the rights of the human being are extinguished with his death, raising the possibility of their recognition through the concept of “transcendent preterit personality” and taking into account the posthumous dignity of the person. To this end, the subject is analyzed both from a theoretical and a practical perspective, offering a more complete perspective in the better defense and protection of the Fundamental Rights, among other issues related to the subject.